Psychedelic: An Illustration that Reveals False Power in Rhythm 0 Performance Art - Dewanto, Thomas Hanandry; Bahruddin, Muhammad (Institut Seni Indonesia Denpasar, 2024)
The performance art entitled Rhythm 0 by Marina Abramovic is controversial, raising various questions regarding its power and influence in the context of art. This research aims to illustrate the microphysical approach to power in the performing arts Rhythm 0, where power emerges from fear and shifts to the dominance of the ideology of power. A qualitative approach with visual analysis techniques was used in this research to explain the phenomenon of this performing arts from a very subjective view. This created illustration entitled